The consumer's perspective on evaluating products: service is the key. Issue 3 (11th May 2015) - Oliver, Jason
Abstract : Purpose: – This paper aims to begin to remedy deficiencies in the understanding of how the increased focus on service, even in manufacturing environments, relates to consumer desire for relationships. The role of relationships in both services and physical goods has taken on a new meaning that should be further explored. Design/methodology/approach: – The qualitative study reported in this paper examines the extent to which consumers feel that they are in relationships with companies from a variety of product categories that range from search goods (easy to evaluate in advance of purchase) to credence goods (difficult to evaluate). The analysis is based on semi-structured interviews with 20 customers. Findings: – The results identify when consumers place an emphasis on specific relational behaviors in evaluating the product use experience. Specifically, trust, commitment and expertise seemed more important when products were difficult to evaluate in advance, whereas social benefits and special treatment were mentioned with search and credence products more than experience products. Research limitations/implications: – The results are exploratory and should be replicated and extended utilizing a larger, more representative sample before they are generalized to market. Practical implications: – The results have important implications for practitioners in both manufacturing and service industries, as they decide when and how to differentiate their service components and pursue relationships with consumers. Firms need to stand out from a service perspective. Originality/value: – The manuscript develops a more robust understanding of the relational behaviors that matter to customers and provides recommendations about how to best manage them.